An analytic problem in combinatorial structures - Manstavičius, Eugenijus; Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2000)
An asymptotical formula for the Taylor coefficients of the generating series appearing in combinatorics is obtained. It is applied to derive a formula for the number of multisets of increasing weight.